Individual, Household, and Contextual Factors Influencing the Timing of the First Antenatal Care Attendance in Northwest Ethiopia: A Two-Level Binary Logistic Regression Analysis - Emiru AA; Alene GD; Debelew GT (Dove Medical Press, 2020)
Amanu Aragaw Emiru,1 Getu Degu Alene,2 Gurmesa Tura Debelew3 1Department of Reproductive Health and Population Studies, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Epidemiology and Biostatistics, College of Medicine and Health Sciences, Bahir Dar University, Bahir, Ethiopia; 3Department of Population and Family Health, Faculty of Public Health, Institute of Health, Jimma University, Jimma, EthiopiaCorrespondence: Amanu Aragaw EmiruDepartment of Reproductive Health and Population Studies, College of Medicine and Health Sciences, Bahir Dar University, P.O. Box: 79, Bahir Dar, EthiopiaTel +251 918780295Email amanuaragaw@yahoo.comBackground: Early antenatal visit is critical for the health and well-being of mothers and babies. However, various individual, family level, and contextual factors influence the timely initiation of antenatal care.Objective: The aim of this study was to examine individual, household, and community-level factors associated with the timing of first ANC visit among mothers who gave birth in the last twelve months before the survey.Methods: A community-based cross-sectional study was conducted in June 2018. A multistage cluster sampling technique was applied, and a sample of 898 women was considered. Data were collected using a questionnaire and checklist. The analysis was made using SPSS. A multilevel logistic regression with random effects at the kebele level was developed to assess the predictors of late initiation of antenatal care. Odds ratio with 95% confidence intervals was used to measure association while the intra-class correlation coefficient and the median odds ratio were used to measure variations.Results: Overall, 78.4% (95% CI: 75.6, 80.9) of women started their first ANC in 4 months of gestation or later and significant heterogeneity was observed between clusters. At level 1, women with intended pregnancy (aOR=0.31; 95% CI: 0.12, 0.79), and being knowledgeable about the timing (aOR=0.43; 95% CI: 0.25, 0.75) and pregnancy-related complications (aOR=0.16; 95% CI: 0.10, 0.26) were less likely to delay their first ANC visit. Conversely, the odds of late ANC visit was higher among women with no formal education (aOR=4.08, 95% CI: 2.20, 7.55). Distance to the health facility (aOR=1.04; 95% CI, 1.01– 1.08) was the only level-2 significant predictor.Conclusion: The study revealed that late ANC initiation was rampant. Several factors operating at different levels were associated with late ANC visits; yet, the role of individual-level factors was relatively stronger. Hence, awareness creation is essential to the underprivileged community using the available communication networks.Keywords: antenatal care, timing, delay, late, multilevel